Power Semiconductor Device Humidity Reliability Study - Wang, Jiale (International Journal of Mechanical and Electrical Engineering, 2024)
This paper aims to study the aging mechanism of power semiconductor devices in high humidity environments, propose anti-humidity optimization design methods, and explore the humidity reliability of these devices in-depth. The reliability of the devices can be examined through High Humidity High Temperature Reverse Bias Testing to simulate aging in high humidity environments and evaluate their performance. By analyzing the performance of power semiconductor devices under humidity stress, this research reveals the humidity aging mechanism and failure points, providing a theoretical basis for optimizing the design to enhance humidity resistance and lifespan [2]. Research on humidity reliability has gained frequent attention in recent years, but the causes and mechanisms of failure in chips are still unclear. Therefore, similar tests are required to analyze and summarize the failure parts. Simulations can be used to model the working conditions of devices in high humidity environments, simulating the diffusion of water vapor into chips, identifying failure patterns, analyzing moisture diffusion mechanisms, and improving the weak points of failure through comparative analysis using different materials. Finally, the most suitable anti-humidity materials can be identified for device improvement.